Productivity performance of wood sawmill industry based on value-added output in Peninsular Malaysia - Pang, Suet Kum (2017)
Wood sawmill industry is the basic link between the raw materials and the end-users of the sawn timber products in Peninsular Malaysia. The efficiency of the wood sawmill industry is crucial to the development of the wood based industries in Malaysia with the export earnings of RM22.1 billion in 2016. Value added manufacturing activities in the wood sawmill industry of Peninsular Malaysia is important to provide employment opportunities, particularly among the low income population living in the rural areas, and to provide returns to the local economy while being environmentally sustainable. This study is a review on the value-added wood sawmill industry in Peninsular Malaysia, based on the estimates of the value of logs and sawn timber in Peninsular Malaysia over the period of 2003 – 2015. The productivity performance measures based on the concept of value added are emphasized in this study. The value added in the wood sawmill industry achieved negative value between 2003 – 2006 and subsequently increased to achieve positive value by year 2007 onwards. This study utilises linear regression to analyze the direction of the long term trend of the value added in the wood sawmill industry in Peninsular Malaysia from 2003 to 2015. A further analysis using the value added productivity measures found that the amount of value added had a significant link to the sawn timber price rather than the number of workers. Based on the findings, Malaysia is paving the right direction to achieve the goal of National Timber Policy 2020 by transforming the timber industry into a high value-added industry.